1990
DOI: 10.1159/000235099
|View full text |Cite
|
Sign up to set email alerts
|

Basophil Releasability in Human Hydatidosis

Abstract: We studied immunoglobulin E (IgE)- and non-IgE-mediated releasability in basophils from 31 patients with hydatidosis. Histamine release to non-IgE-dependent stimuli did not differ significantly between normal individuals and patients with hydatidosis. On the contrary, an increased histamine liberation was obtained by challenging basophils from hydatid patients with anti-human IgE. It is concluded that Echinococcus granulosus infection induces an enhanced sensitivity of basophils to IgE-dependent stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Regarding basophils, the human basophil degranulation test was found to be positive in 33% of patients with hydatid disease (HD)[ 19 ]. Furthermore, evidence of increased histamine release from hydatid patient basophils following a challenge with anti-human IgE has also been obtained[ 20 ]. It can be concluded that both the generation of histamine releasing factor (HiRF) and production of IgE, which can bind cytokines, may be involved in this stage of infection[ 21 ].…”
Section: Immune Response To E Granulosus Infectiomentioning
confidence: 99%
“…Regarding basophils, the human basophil degranulation test was found to be positive in 33% of patients with hydatid disease (HD)[ 19 ]. Furthermore, evidence of increased histamine release from hydatid patient basophils following a challenge with anti-human IgE has also been obtained[ 20 ]. It can be concluded that both the generation of histamine releasing factor (HiRF) and production of IgE, which can bind cytokines, may be involved in this stage of infection[ 21 ].…”
Section: Immune Response To E Granulosus Infectiomentioning
confidence: 99%
“…The generation of histamine releasing factor may ac count for the enhanced basophil releasability we have ob served in patients with E. granulosus infection [7]. Indeed, it is postulated that the production of this factor in vivo may also lead to the increased releasability of histamine by basophils reported in some patients with atopic dermatitis and to the cutaneous hyperreactivity seen in many such patients [15].…”
Section: Discussionmentioning
confidence: 86%
“…We have shown that Echinococcus granulosus infection can induce an enhanced sensitivity of basophils to IgEdependcnt stimuli [7]. Indeed, this hypcrrcleasable state makes it possible to obtain a high response to appropriate antigen, even though levels of cell-bound IgE are low [8].…”
Section: Introductionmentioning
confidence: 98%